The compressibility and strength characteristics of Diliman shale - Chantalakhana, Charoen
In many areas, shale is sandwiched by tuff layers. This shale may, in many cases, form the subgrade for road of runway pavements, or the foundation soil for buildings. In order to study the compressibility and strength characteristics of shale, an investigation has been performed on several undisturbed samples. The testing program included consolidation test and triaxial test. It was found that soil sample are overconsolidated by nature.